Regional Remote Sensing Analysis of Fault Tectonics in theNorthwestern Part of the Verkhoyan-Kolyma Orogenic Regionand Assessment of Its Role in Ore Formation - Minaev Vasilii; Ustinov Stepan; Petrov Vladislav; Svecherevsky Alexey; Nafigin Igor; Manevich Aleksandr; Akmatov Dastan (Russian Journal of Earth Sciences, 2025)
The article presents the results of a comprehensive analysis of fault tectonics in the north-western part of the Verkhoyan-Kolyma orogenic region. The studies were performed on a regional scale. Based on a digital relief model, lineaments were identified manually and automatically. The results obtained in combination with literature data allowed us to perform tectonophysical recon-structions using the model of P. L. Hancock (1985). Based on the reconstructions, we determined the expected areas of tectonic structures that had the highest hydraulic activity during collision processes, which are presumably associated with gold deposits and ore occurrences in Eastern Yakutia. Areas promising for the discovery of new ore objects were identified.